Microwave-photonic networks based on single-mode multi-core optical fibers - Zakrzewski, Zbigniew (Photonics Letters of Poland, 2013)
In the paper, the proposition of construction of the 9-core single-mode optical fiber TA-MCF (Trench Assisted ? Multi-Core Fiber) have been presented. Nine-core TA-MCF can be used to connecting the multi-antenna array modules to the radio-photonic modems located at the signal processing central. Optical networks for transporting of the radio signals, called RoF (Radio over Fiber) Networks, allow the space distributing of the radio base-station eNodeB on the greater area. Multi-core fibers give possibility for efficient realization of such solutions. Full Text: PDF References J. Cooper, "Fiber/Radio for the provision of cordless/mobile telephony services in the access network", Electron. Lett., vol. 26, no. 24, pp. 2054-2056 (1990) DirectLink S. Randel, R. Ryf, A. H. Gnauck, M. A. Mestre, C. Schmidt, R.-J. Essiambre, P. J. Winzer, R. Delbue, P. Pupalaikis, A. Sureka, Y. Sun, X. Jiang, and R. Lingle, "Mode-multiplexed 6x20-GBd QPSK transmission over 1200-km DGD compensated few-mode fiber", in Proc. OFC/NFOEC (2012) L. Maksymiuk, J. Siuzdak, "Successful IEEE 802.11n 2-channel MIMO transmission over standard graded index multimode fiber in passband", Communications (QBSC), 2012 26th Biennial Symposium on, pp. 15-18, (2012) CrossRef T. Hayashi, T. Taru, O. Shimakawa, T. Sasaki, and E. Sasaoka, "Design and fabrication of ultralow crosstalk and low-loss multi-core fiber", Opt. Express, vol. 19, no. 17, pp. 16576?16592, (2011) CrossRef K. Saitoh, M. Koshiba, K. Takenaga, and S. Matsuo, "Crosstalk and Core Density in Uncoupled Multicore Fibers", IEEE Photonics Tech. Letters, Vol. 24, No. 21, pp. 1898-1901, (2012) CrossRef K. Takenaga,Y. Arakawa, Y. Sasaki, S. Tanigawa, S.Matsuo, K.Saitoh, and M. Koshiba, "A large effective area multi-core fiber with an optimized cladding thickness", Opt. Express, vol. 19, no. 26, pp. B542?B550, (2011) CrossRef